2021
DOI: 10.46542/pe.2021.211.276282
|View full text |Cite
|
Sign up to set email alerts
|

Impact of using debates in a pharmacoeconomic course on students’ self-reported perceptions of skills acquired

Abstract: Objective: To explore the impact of debates on students’ perceptions of their (i) ability to read and critically appraise pharmacoeconomic literature and (ii) confidence in synthesising evidence, reaching a decision, and communicating it effectively. Methods: 77 pharmacoeconomics course students participated in a debate exercise: one team for adding a medication to a formulary and the other against adding. The self-reported perceptions of skills acquired were evaluated via pre- and post-debate questionnaires.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The debate strategy employed in this study also generated deep and thoughtful comments from participants intimating two things: (1) they had developed a solid understanding of the issues via collectively engaging with their learning partners (see Fauzan, 2016;Mahmood et al, 2011;Onen, 2016) and (2) the debate seemed to provide a rigorous learning environment where students could assume responsibility for their own learning (see Lea et al, 2003;O'Neill & McMahon, 2005;Onen, 2016). Alaqeel et al (2021) also found that debating improved Saudi female students' perceptions of their confidence in reasoning and communicating their arguments.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The debate strategy employed in this study also generated deep and thoughtful comments from participants intimating two things: (1) they had developed a solid understanding of the issues via collectively engaging with their learning partners (see Fauzan, 2016;Mahmood et al, 2011;Onen, 2016) and (2) the debate seemed to provide a rigorous learning environment where students could assume responsibility for their own learning (see Lea et al, 2003;O'Neill & McMahon, 2005;Onen, 2016). Alaqeel et al (2021) also found that debating improved Saudi female students' perceptions of their confidence in reasoning and communicating their arguments.…”
Section: Discussionmentioning
confidence: 88%
“…, 2003; O’Neill & McMahon, 2005; Onen, 2016). Alaqeel et al . (2021) also found that debating improved Saudi female students’ perceptions of their confidence in reasoning and communicating their arguments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This positive outcome was also deduced from the self-reflection clause in the post-debate questionnaire, which is a common method for assessing the positivity of such activities. 6 , 15 , 21 Some of the students’ response demonstrated considerable empirical evidence that their abilities to review medical information, formulate an argument and work as part of a team improved greatly during the preparation for the debate as well as during the session.…”
Section: Discussionmentioning
confidence: 99%
“… 24–26 Pharmacy students responded positively when using debate as a teaching tool for improving communication skills, teamwork, critical evaluation of the literature and a better understanding of controversial issues. 6 , 21 …”
Section: Discussionmentioning
confidence: 99%